Some Aspects Regarding the Waste Pollution of Rivers in Romania: Array - Dorobăț, Leonard Magdalin; Turtureanu, Anca; Dobrescu, Codruța Mihaela (Journal of Danubian Studies and Research, 2020)
The issue of the plastic waste, PET bottles, food packing dump that is carried by the flowing waters in Romania is older and still rigorous. Causes are represented by the irresponsible throwing, in the environment, of wastes by the local inhabitants, tourists, and sometimes, paradoxically, by some of the authorities. Considering that these wastes pollute the areas in the rivers’ proximity, some reservoirs, the riverbed of the Danube and that most of the reach the Black Sea, things seem to be more stringent. A significant part of the plastic is turned into micro particles which are spread in the environment, ending swallowed by humans and animals, leading to serious effects on the health. Economic losses generated by dump accumulation in tourism or from the problems generated against hydroelectric plants are also significant. Moreover, in some cases, it might lead to cross-border problems, as waste reaches the territories of neighboring states through flowing waters, especially due to flash floods and floods. Solving these issues involves more aspects, from the awareness of the causes of some citizens’ irresponsible behavior to finding solutions and involving all the responsible factors.